Consistent behavioural differences between migratory and resident hoverflies - Odermatt, J.; Frommen, J.; Menz, Myles (Elsevier Ltd., 2017)
Many animals differ consistently in the way they behave across time and context. This animal personality has been linked to traits such as life history strategies or dispersal. However, few studies have addressed the relationship between consistent behavioural differences and migration. This is of particular interest with respect to partial migration, in which only part of a population migrates while the other remains resident. We investigated whether two behavioural traits (activity and stress response) are consistent across time in individuals of two partially migratory hoverfly species, Episyrphus balteatus and Scaeva selenitica. We also investigated whether there were consistent behavioural differences between migratory and resident flies within species. Individual activity was consistent across time in both species. Additionally, activity of female E. balteatus differed between the phenotypes, with summer insects being more active than migrating and overwintering individuals in our assays. Furthermore, females of S. selenitica were more active and less easily stressed than E. balteatus. The results not only highlight that hoverflies behave consistently across time, but also that behavioural differences also occur between migratory and resident flies. They also provide evidence for the possible role of behavioural differences in influencing partial migration decisions within populations.